Challenges and strategies to optimize the figure of merit: Keeping eyes on thermoelectric metamaterials. (1st November 2022) - Giri, Karan; Wang, Yan-Lin; Chen, Tsung-Han; Chen, Chun-Hua
Abstract: Thermoelectric materials have been recognized as promising materials and make a prime contribution to converting waste heat into useful electrical energy without any further loss. In recent decades, researchers have witnessed the development of new and efficient mechanisms/strategies to optimize the figure of merit of these materials to recover the low-grade heat more efficiently. A balanced trade-off between TE parameters is indispensable to optimizing the ZT value. To some extent, the hit and trial method can be effective to optimize the TE properties. In electronic band engineering; the band convergence, the curvedness of the bandgap, or effective mass manipulation, significantly optimizes the power factor. Similarly, hierarchical scattering and low-dimensionality techniques are effective strategies to reduce thermal conductivity. It is better to pay more attention to the lattice thermal conductivity part rather than other TE properties to optimize the ZT value. For this one of the approaches is the introduction of various scales of defects in the specimen which scatter the phonons of all wavelengths. Finally, the notion of synthesizing TE metamaterials might bring a revolution in the TE materials system by mounting the ZT value to the threshold of 3.0.